Groups for the dead. (September 2020) - Gerada, Clare; Griffiths, Frances
This article 2 describes a group for those bereaved following the death through suicide of a doctor. It describes why it was formed, how it links to Foulkes' matrix and, the conscious and unconscious processes which take place. This was the first gathering of a group of this kind in the United Kingdom.